2014
DOI: 10.1051/fruits/2014012
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal efficacy of botanicals against major postharvest pathogens of Kinnow mandarin and their use to maintain postharvest quality

Abstract: -Introduction. Kinnow is an important citrus crop grown in India, which suffers from several postharvest diseases during storage. Hence, an attempt was made to combat such diseases with the botanicals Aloe vera, Eucalyptus and Ocimum on Kinnow mandarin to prolong its availability for a longer time. Materials and methods. For this, in vitro and in vivo studies were conducted. The poisoned food technique was used for in vitro studies, and, for in vivo studies, Kinnow fruit were pre-inoculated with pathogens (Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…Early work by Saks and Barkai-Golan (1995) showed significant activity of A. vera gels against P. digitatum and against green mold on grapefruits artificially inoculated with this fungus. Recently, Jhalegar et al (2014) found that an A. vera-based coating reduced green and blue molds on mandarins. Other research showed the in vitro inhibitory activity of A. vera gels against the most important postharvest pathogens of stone fruits and table grapes, and also the high antifungal action of preharvest or postharvest coating applications of these gels on several species of stone fruits (Martínez-Romero et al, 2006;Guillén et al, 2013), table grapes (Valverde et al, 2005), strawberries (Sogvar et al, 2016), and avocados (Bill et al, 2014).…”
Section: Aloe Spp Coatingsmentioning
confidence: 99%
“…Early work by Saks and Barkai-Golan (1995) showed significant activity of A. vera gels against P. digitatum and against green mold on grapefruits artificially inoculated with this fungus. Recently, Jhalegar et al (2014) found that an A. vera-based coating reduced green and blue molds on mandarins. Other research showed the in vitro inhibitory activity of A. vera gels against the most important postharvest pathogens of stone fruits and table grapes, and also the high antifungal action of preharvest or postharvest coating applications of these gels on several species of stone fruits (Martínez-Romero et al, 2006;Guillén et al, 2013), table grapes (Valverde et al, 2005), strawberries (Sogvar et al, 2016), and avocados (Bill et al, 2014).…”
Section: Aloe Spp Coatingsmentioning
confidence: 99%
“…When the mandarin samples were stored at 4°C for 35 days, P. digitatum growth was not observed on any fruit surface, indicating no identifiable inhibitory effects of the treatments against P. digitatum growth at this temperature (data not shown). This likely occurred because P. digitatum exhibits reported difficulty growing at temperatures below 10°C (Jhalegar, Sharma, & Singh, 2014). Figure 2 shows the effects of GSE/CW coating with or without CaO washing on the growth of P. digitatum inoculated on mandarin samples during storage for 14 days at 25°C.…”
Section: Resultsmentioning
confidence: 99%
“…There is no published literature about the V. vinifera and cactus gel, whereas high potential of A. vera gel on the prevention of microbial spoilage was previously noted for other fruits and vegetables, i.e. tomato (Chrysargyris et al 2016), citrus (Jhalegar et al 2014), raspberry (Hassanpour et al 2015), and readyto-eat pomegranate arils (Martínez-Romero et al 2013). Reduction of the microbial decay is indispensable for prolonging the safe storage of fresh-cut products (Li et al 2018).…”
Section: Discussionmentioning
confidence: 99%